Mr. Popper's penguins - Atwater, Richard; Atwater, Florence; Lawson, Robert (New York Little, Brown and Co., 2009)
The unexpected delivery of a large crate containing an Antarctic penguin changes the life and fortunes of Mr. Popper, a house painter obsessed by dreams of the Polar regions.
Originally published: Boston : Little, Brown and Co., 1938.
Keywords: Penguins; American Fiction in English; Humorous stories